2012
DOI: 10.1002/jts.21667
|View full text |Cite
|
Sign up to set email alerts
|

Does physiologic response to loud tones change following cognitive–behavioral treatment for posttraumatic stress disorder?

Abstract: This study examined responses to loud tones before and after cognitive–behavioral treatment for posttraumatic stress disorder (PTSD). Seventy-four women in a PTSD treatment outcome study for rape-related (n = 54) or physical assault-related PTSD (n = 20) were assessed in an auditory loud tone paradigm. Assessments were conducted before and after a 6-week period of cognitive–behavioral therapy. Physiologic responses to loud tones included heart rate (HR), skin conductance (SC), and eye-blink electromyogram (EMG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 36 publications
2
18
1
Order By: Relevance
“…Future research should consider obtaining HRV prior to presenting the loud tone stimuli, so as to allow for an examination of the relationship between HRV and heart rate reactivity to the loud tones. From prior research, it is known that decreased parasympathetic tone is associated with PTSD and that this changes with treatment (Griffin et al, 2012). Experiments in which parasympathetic tone were to be modified, e.g., by drugs, and the effect on nightmares measured, could help clarify causation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Future research should consider obtaining HRV prior to presenting the loud tone stimuli, so as to allow for an examination of the relationship between HRV and heart rate reactivity to the loud tones. From prior research, it is known that decreased parasympathetic tone is associated with PTSD and that this changes with treatment (Griffin et al, 2012). Experiments in which parasympathetic tone were to be modified, e.g., by drugs, and the effect on nightmares measured, could help clarify causation.…”
Section: Discussionmentioning
confidence: 99%
“…Data were obtained in the context of a cognitive behavioral therapy study of women with PTSD resulting from rape or physical assault (n=150) (Griffin, Resick, & Galovski, 2012; Resick et al, 2008). A subset of these women (n=73) were tested in the psychophysiology laboratory prior to beginning therapy by measuring their HR, SC and EMG responses during exposure to a series of loud tones.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 A recent study that examined psychophysiological responses before and after cognitive-behavioral therapy for PTSD found that treatment responders showed a significant reduction in eye-blink EMG, heart rate, and skin conductance responses to loud tones, whereas treatment non-responders did not. 14 Understanding discordances between psychophysiological and subjective measures of treatment outcome will require further research. Pre-treatment psychophysiological assessments might be examined for their usefulness in guiding treatment selection.…”
Section: Psychophysiological Studiesmentioning
confidence: 99%